2009
DOI: 10.1002/mc.20582
|View full text |Cite
|
Sign up to set email alerts
|

Cold‐inducible RNA‐binding protein contributes to human antigen R and cyclin E1 deregulation in breast cancer

Abstract: The cell cycle regulator cyclin E1 is aberrantly expressed in a variety of human cancers. In breast cancer, elevated cyclin E1 correlates with poor outcome, as do high cytoplasmic levels of the stress-induced RNA binding protein Human antigen R (HuR). We showed previously that increased cytoplasmic HuR elevates cyclin E1 in MCF-7 breast cancer cells by stabilizing its mRNA. We show here that cold-inducible RNA binding protein (CIRP) co-regulates cyclin E1 with HuR in breast cancer cells. CIRP had been shown to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 46 publications
3
47
0
2
Order By: Relevance
“…Gene ontology analysis indicated that all 5 transcripts were associated with stress responses (Table 2). None of these transcripts had been linked to CIRBP previously but the general association with stress responses is consistent with the proposed role of CIRBP in responding to cellular stress [15][17], [38]. The present work further supports this general concept.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Gene ontology analysis indicated that all 5 transcripts were associated with stress responses (Table 2). None of these transcripts had been linked to CIRBP previously but the general association with stress responses is consistent with the proposed role of CIRBP in responding to cellular stress [15][17], [38]. The present work further supports this general concept.…”
Section: Discussionsupporting
confidence: 89%
“…We had anticipated that this strategy would lead to the identification of mRNAs bound directly by CIRBP [15]-[17], [38]. However, IL-1β is a key cytokine that modulates the expression of other secondary cytokines including IL-8 and TNFAIP6 [26], [27].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells often further their survival and growth in hostile environments by increasing the expression of key SRFs such as CIRP, HSF1, HIF1, and NRF2 (45)(46)(47)(48). One of the consequences of SRF expression in hypoxic cancer cells is increased mutagenesis (29), similar to the SIM of TNRs observed here.…”
Section: Discussionsupporting
confidence: 56%
“…In addition to transcriptional control, cyclin E1 mRNA stability is positively regulated in breast cancer cells by the RNA binding proteins HuR and CIRP [17, 27]. To ask if regulation of these proteins could also underlie changes in cyclin E1, we assessed their relative protein levels.…”
Section: Resultsmentioning
confidence: 99%